2-(2,5-Dimethoxyphenyl)-N-[2-(4-hydroxyphenyl)ethyl]acetamide - Choi, Hyeong (International Union of Crystallography, 2012)
In the title compound, C(18)H(21)NO(4), the dihedral angles between the acetamide group and the methoxy- and hydroxy-substitured benzene rings are 80.81 (5) and 8.19 (12)°, respectively. The benzene rings are twisted with respect to each other, making a dihedral angle of 72.89 (5)°. In the crystal, N—H⋯O and O—H⋯O hydrogen bonds link the molecules into a three-dimensional network.